2021
DOI: 10.1021/acs.iecr.1c02265
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Triazine-Based H2S Scavengers via Raman Spectroscopy

Abstract: MEA-triazine is a commonly used hydrogen sulfide scavenger for oil and gas applications. It is nonregenerative: it is consumed during the gas sweetening process. We describe a new technique to quantify MEA-triazine concentration using Raman spectroscopy. The method is robust, covering triazine concentrations ranging from 30% to 80% (by mass), while additionally enabling quantification of residual reactants. This method is the first demonstration of MEA-triazine concentration analysis in industrially relevant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Amines arrive at the refinery from multiple sources, as naturally occurring compounds, corrosion control materials, or residuals from upstream treatments. These tramp amines are most commonly present in the crude as remnants of upstream hydrogen sulfide scavenging, 1 and they can be especially problematic for refineries handling heavy, sour crudes. 2 Amines are also used for corrosion control within the refinery, leading to additional amine content from contamination and unit leakage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Amines arrive at the refinery from multiple sources, as naturally occurring compounds, corrosion control materials, or residuals from upstream treatments. These tramp amines are most commonly present in the crude as remnants of upstream hydrogen sulfide scavenging, 1 and they can be especially problematic for refineries handling heavy, sour crudes. 2 Amines are also used for corrosion control within the refinery, leading to additional amine content from contamination and unit leakage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…19 In another report, the quantification of HET-TRZ in the range of 30−80 wt % using Raman spectroscopy has been described. 20 The method proved to be very useful for the quality control of triazinebased commercial H 2 S scavengers and the quantification of residual reactants during the scavenging process. On the other hand, a recent study showed the possibility of detecting ppm levels of amines in refinery wastewaters using the ultrasensitive surface-enhanced Raman spectroscopy (SERS) technique, 21 laying the groundwork for the detection of ultralow levels of substituted 1,3,5-triazines or other known nitrogen-containing H 2 S scavengers in downstream processes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Raman spectroscopy has been used not only as a qualitative tool but also to provide information regarding the composition of the triazine-based spent fluid to optimize the operational conditions in bubble tower contactors for gas sweetening . In another report, the quantification of HET-TRZ in the range of 30–80 wt % using Raman spectroscopy has been described . The method proved to be very useful for the quality control of triazine-based commercial H 2 S scavengers and the quantification of residual reactants during the scavenging process.…”
Section: Introductionmentioning
confidence: 99%